Power consumption modeling of an Arctic Trucks vehicle - Guðmundsson, Aron Steinn (My University, 2019)
In this thesis a model is created to simulate the power demand and fuel consumption of an Arctic Trucks vehicle. The model is created in Matlab Simulink using the QSS toolbox developed by ETH Zurich. A specific off-road driving cycle is created and investigated to verify the model as well as to investigate the power demand and fuel consumption. Arctic Trucks manufactures modified SUV and pickup trucks for off-road driving. Their vehicles are used for in extreme conditions where large tyres and associated modifications are needed. Arctic Trucks wanted to investigate the potential benefits of using hybrid vehicles and the model created in this thesis can be used to estimate the required hybrid powertrain size needed for such vehicles, that is, the battery and motor size. The model created was capable of estimating the power demand and fuel consumption with at least 95% accuracy for a typical off-road driving cycle in snowy conditions.
Keywords: Hybrid, power demand, vehicle modeling, fuel consumption, hybrid modeling, Simulink, QSS Toolbox